Calprotectin levels in rheumatoid arthritis and their correlation with disease activity: a meta-analysis. Issue 5 (4th July 2017) - Bae, Sang-Cheol; Lee, Young Ho
ABSTRACT: Objective : We evaluated the relationship between calprotectin levels and rheumatoid arthritis (RA), and the correlation between plasma/serum calprotectin and RA activity. Methods : We searched PUBMED, EMBASE, and Cochrane databases and performed meta-analyses comparing plasma/serum or synovial fluid calprotectin levels in RA patients and controls, and correlation coefficients between calprotectin levels and disease activity for 28 joints (DAS28) as well as C-reactive protein (CRP) in RA patients. Results : Sixteen studies including 849 RA patients and 266 controls were available for meta-analysis. Meta-analysis showed that calprotectin levels were significantly higher in the RA group than in the control group (SMD = 2.337, 95% CI = 1.544–3.130, p  < 1.0 × 10 –8 ). Stratification by rheumatoid factor (RF) status revealed significantly elevated calprotectin levels in the RF-positive RA group compared to that of the RF-negative RA group (SMD = 0.574, 95% CI = 0.345–0.804, p  = 9.2 × 10 –7 ). Meta-analysis of correlation coefficients identified a significant positive correlation between calprotectin levels and CRP or DAS28 (correlation coefficient for CRP = 0.566, 95% CI = 0.512–0.615, p  < 1.0 × 10 –8 ; correlation coefficient for DAS28 = 0.438, 95% CI = 0.269–0.518, p  = 2.5 × 10 –6 ). Calprotectin levels in synovial fluid were significantly higher in the RA group than in the control group (SMD = 2.891, 95% CI = 1.067–4.715, p  = 0.002). Conclusions : Our meta-analysis demonstrates that circulating and synovial fluid calprotectin levels are high in patients with RA, and that circulating calprotectin levels positively correlate with RA activity.